Systemic antibody responses to gut commensal bacteria during chronic HIV-1 infection. Issue 11 (21st April 2011) - Haas, Anna; Zimmermann, Kathrin; Graw, Frederik; Slack, Emma; Rusert, Peter; Ledergerber, Bruno; Bossart, Walter; Weber, Rainer; Thurnheer, Maria C; Battegay, Manuel; Hirschel, Bernard; Vernazza, Pietro; et al.
Abstract : Background: Human systemic antibody responses to commensal microbiota are not well characterised during health and disease. Of particular interest is the analysis of their potential modulation caused by chronic HIV-1 infection which is associated with sustained enteropathy and systemic B cell disturbances reflected by impaired B cell responses and chronic B cell hyperactivity. The mechanisms underlying B cell hyperactivation and the specificities of the resulting hypergammaglobulinaemia are only poorly understood. Methods: By a technique referred to as live bacterial FACS (fluorescence-activated cell sorting), the present study investigated systemic antibody responses to several gut and skin commensal bacteria as well as Candida albicans in longitudinal plasma and serum samples from healthy donors, chronic HIV-1-infected individuals with or without diarrhoea and patients with inflammatory bowel disease (IBD). Results: The data show that systemic antibody responses to the commensal microbiota were abundantly present in humans and remained remarkably stable over years. Overall systemic antibody responses to gut commensal bacteria were not affected during chronic HIV-1 infection, with titres decreasing when normalised to elevated plasma immunoglobulin G (IgG) levels found in patients with HIV. In contrast, increases in the titres of high affinity antimicrobiota antibodies were detected in patients with IBD, demonstrating that conditions with known increased intestinal permeability and aberrant mutualism can induce changes in antibody titres observed in these assays. Conclusion: Neither HIV-associated enteropathy nor B cell dysfunction impact on the high-affinity systemic antibody responses to gut commensal bacteria. HIV-associated hypergammaglobulinaemia is therefore unlikely to be driven by induction of antimicrobiota antibodies.